Formulasi Krim Anti-Aging Pada Kulit Daerah Tropis Berbasis Ekstrak Daun Kelor, Minyak Kenanga Dan Minyak Lemon Sebagai Bioaktif - Vivi Nurhadianty; Herwinda Brahmanti; Sinta Murlistyarini; Safira Khanza; Citra Wahyu Rizkita; Chandrawati Cahyani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2021)
Loss of moisture in the skin and exposure to high UV rays can cause dry, thin, inelastic skin and wrinkles. Proper anti-aging cream can reduce and prevent skin damage. Moringa leaf extract and cananga oil have specific bioactive properties such as antioxidants and antibacterials. Meanwhile, lemon oil is high in vitamin C and can improve the collagen structure in the skin. To produce anti-aging cream, essential oils as active ingredients are added with various compositions and then formulated and on the skin of the dorsal hand. The results showed that the cream produced was homogeneous but still required the addition of an emulsifier. The cream also meets SNI in terms of pH. The creams in formulas 7 and 9 provide significant results in reducing the level of aging. In this study, it needs to take a longer time to determine the stability of the cream.